Activation-free fabrication of high-surface-area porous carbon nanosheets from conjugated copolymers. Issue 81 (24th September 2018) - Tang, Youchen; Liu, Shaohong; Zheng, Bingna; Liu, Ruliang; Fu, Ruowen; Wu, Dingcai; Zhang, Mingqiu; Rong, Minzhi
Abstract : Porous carbon nanosheets with a high surface area of 1606 m 2 g −1 have been successfully prepared by direct carbonization of graphene oxide sandwiched poly(aniline- co -pyrrole). Abstract : High-surface-area porous carbon nanosheets have been successfully prepared by direct carbonization of graphene oxide sandwiched poly(aniline- co -pyrrole). Benefiting from the distinct structure features of the poly(aniline- co -pyrrole) and its homogeneous deposition on the graphene oxide surface, the surface area of the porous carbon nanosheets is as high as 1606 m 2 g −1 .